The Effect Of Giving Tamarind Turmeric Herbal Medicine To Decrea Dysmenorrhea In Midwifery Students At Megarezky University - Mirna Jamal; Fadjriah Ohorella; Amina Ahmad; Rahmawati . (JURNAL KEBIDANAN KESTRA (JKK), 2022)
Adolescence is a period of change or transition from children to adulthood Including biological, psychological, and social changes. Changes that often occur in women after entering adolescence are the devolopment of the reproductive organs which is marked by the onset of menstruation. Menstruation that occurs in women is a periodic discharge of blood from the uterus through the vagina which is characterized by pain before and during menstruation and menstrual pain usually occurs due to endometriosis, pelvic inflammatory disease, excessive stress, hormonal imbalances and abnormalities on the uterus. This study was conducted with the aim of knowing the effect of giving turmeric acid to reduce dysmenorrhea in Midwifery students at Megarezky University. The research method used is Quasi Eksperiment with a pre-test post-test design technique without a control group. The population in this study were 43 students and the sample was 30 students using the purposive sampling technique and for data collection, it was collected by means of observation. The results of the post-test average value are smaller than the pre-test average value, which is 3,05 for the post-test value and 4,75 for the pre-test value, while the Wilcoxon test results obtained a value of ?=0,000 < ?=0,05 (p < ?), so that H0 is rejected, which means that there is an effect of giving turmeric acid to decrease dysmenorrhea in midwifery students at Megarezky University.